Aceruloplasminaemia with progressive atrophy without brain iron overload: treatment with oral chelation. Issue 4 (2nd October 2007) - Skidmore, F M; Drago, V; Foster, P; Schmalfuss, I M; Heilman, K M; Streiff, R R
Abstract : Background: Hereditary aceruloplasminaemia is a disorder of iron metabolism that is characterised by iron accumulation in the brain and other visceral organs. In previously reported cases, individuals with the disorder were noted to have evidence of iron accumulation in the brain. Oral chelating agents have not been used in neurological diseases of iron metabolism. Methods: A 54-year-old woman who presented with ataxia, lower extremity spasticity and chorea was evaluated for evidence of the source of neurological dysfunction. Results: Blood studies revealed no detectable ceruloplasmin. Marked iron overload was defined by a liver biopsy, which showed a variegated pattern consistent with a primary cause of iron overload. Review of MRI scans showed progressive brain atrophy without visible iron accumulation occurring over a 5-year period. The history suggested that neurodegeneration was coincident with aggressive oral iron replacement. Oral chelation improved many symptoms. Conclusions: Our findings in this patient suggest that disorders of iron transport such as aceruloplasminaemia can be a cause of neurological symptoms such as chorea and cognitive decline, as well as progressive neurodegeneration in the absence of visible iron on MRI scans. We found that oral iron chelation was effective at improving symptoms.